Risk and protective factors associated with domestic abuse among older Chinese in the People's Republic of China. (May 2019) - Fang, Boye; Yan, Elsie; Lai, Daniel W.L.
Highlights: Abuse is common in this sample of 1002 older Chinese with cognitive or physical impairments: Rates mutually reported by care-recipients and caregivers were 9.7%, 0.8%, 33.2%, and 39.7% for psychological abuse, physical abuse, financial exploitation, and caregiver neglect respectively. Both similar and distinct factors were observed for different forms of abuse. Caregiver burden, care recipient neuropsychiatric symptoms, and cognitive impairments are prominent risk factors across different forms of abuse. Protective factors associated with multiple abuse subtypes include caregiver's use of emotion-focused and solution-focused coping, perception of familism, and premorbid relationship rewards. Distinct factors were also observed for respective forms of abuse: Psychological abuse with family poverty; Caregiver neglect with caregiver's substance use and poor physical health; Financial exploitation with caregiver's neurotic personality, care recipient's younger age, absence of chronic illness, and co-residence between the caregiver and care recipient. Abstract: Objectives: To identify risk and protective factors associated with elder abuse among older Chinese with cognitive and physical impairment in the People's Republic of China (PRC). Methods: 1002 dyads of care recipients and family caregivers were interviewed. Results: The mutually reported rates were 9.7%, 0.8%, 33.2%, and 39.7% for psychological abuse, physical abuse, financial exploitation, and caregiver neglect respectively. Caregiver burden, care recipient neuropsychiatric symptoms, and cognitive impairments are prominent risk factors, while protective factors associated with multiple abuse subtypes include caregiver's use of emotion-focused and solution-focused coping, perception of familism, and premorbid relationship rewards. Distinct factors were observed for respective forms of abuse. Psychological abuse with family poverty; Caregiver neglect with caregiver's substance use and poor physical health; Financial exploitation with caregiver's neurotic personality, as well as care recipient's younger age, absence of chronic illness, and co-residence between the caregiver and care recipient. Discussion: Both similar and distinct factors were observed for different forms of abuse, potentially useful for designing prevention and intervention programs.